Parallel mothers [videorecording (DVD)] - Almodóvar, Pedro; Cruz, Penélope; Palma, Rossy de; Sánchez-Gijón, Aitana; Smit, Milena; Elejalde, Israel, 1973- (Sony Pictures Home Entertainment, 2022)
The lives of two single women become intertwined when they share a hospital room giving birth to their daughters on the same day.